Fundamentals of Human Resource Management, Global Edition - Dessler, Gary (Pearson International Content, 2019)
Fundamentals of Human Resources Management supports human resources training for all students of management -- not just HR managers. The text presents a wide range of HR topics within a single semester of material, and a wealth of functional examples and applications. Fundamentals is also the first text of its kind to make talent management processes a core study. This 5th Edition has been updated with practical personnel techniques, real company examples, and new material on business sustainability. Each chapter touches on important recurring themes in management, including employee engagement tactics, small/global business management, employment law features, and positive employee relations, to help students become stronger and more effective managers. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.